The Influence or Organizational Culture and Organizational Commitment on Employee Performance with Competence as a Mediation Variable at Regional Office V BKN Jakarta - Irma Ningsih; Iwan Kurniawan Subagja; Dhistianti Mei. R (Jurnal Ekonomi Manajemen Sistem Informasi, 2025)
This study aims to: 1) identify and analyze the influence of organizational culture on employee performance, 2) identify and analyze the influence of organizational commitment on employee performance, 3) identify and analyze the influence of organizational culture on competency, 4) identify and analyze the influence of organizational commitment on competency, 5) identify and analyze the influence of competency on employee performance, 6) identify and analyze the influence of organizational culture on employee performance through competency, and 7) identify and analyze the influence of organizational commitment on employee performance through competency. The study was conducted at the Regional Office V BKN Jakarta with a sample of 82 respondents. The sampling technique used was saturated sampling. The data analysis methods used were descriptive and path analysis. The results of the study indicate that: 1) organizational culture influences employee performance, 2) organizational commitment influences employee performance, 3) organizational culture influences competency, 4) organizational commitment influences competency, 5) competency influences employee performance, 6) organizational culture influences employee performance through competency, and 7) organizational commitment influences employee performance through competency.